Low intensity laser therapy is comparable to bromcriptine evening primrose oil for the treatment of clyclical mastalgia in Egyptian females - Saied, G M (Tanzania Journal of Health Research, 2008)
No Abstract. Tanzania Health Research Bulletin Vol. 9 (3) 2007: pp. 196-201